2021
DOI: 10.1039/d0ra08873k
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of inulin-type on the iron bioavailability in anemic female rats fed bio-yogurt

Abstract: It is well-documented that iron deficiency leads to anemia, which is the utmost critical problem of nutrition worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In another study in 2020, the researchers tried to determine the effects of iron fortified yogurt (supplemented with short chain fatty acids produced by prebiotics) on various blood parameters of anemic rats. The results of this study showed that not only the hemoglobin and hematocrit levels of anemic rats were improved after consumption of fortified yogurt, but also the Red blood cell count was significantly improved (Mohammed, Dyab, Kheadr, & Dabour, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…In another study in 2020, the researchers tried to determine the effects of iron fortified yogurt (supplemented with short chain fatty acids produced by prebiotics) on various blood parameters of anemic rats. The results of this study showed that not only the hemoglobin and hematocrit levels of anemic rats were improved after consumption of fortified yogurt, but also the Red blood cell count was significantly improved (Mohammed, Dyab, Kheadr, & Dabour, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…The effect of inulin on iron absorption has also been investigated in animals. A study by Mohammed et al, showed that the addition of inulin to yogurt with Fe 2 (SO 4 ) 3 administered to rats increased the bioavailability of iron, and the greatest effect was observed in the case of long-chain inulin [ 48 ] ( Table 2 ). The effect of increased iron absorption in the intestine after inulin ingestion in rats was also shown by Freitas et al [ 49 ] ( Table 2 ).…”
Section: Prebiotics In Anemiamentioning
confidence: 99%
“…has been successfully tested for the production of folate-enriched fermented dairy products [ 67 ]. The addition of Lactobacillus acidophilus in food has been correlated with higher levels of vitamin B12 and folate serum (postbiotic) ( p < 0.05) and decreased anemia prevalence ( p < 0.01) [ 48 , 68 ].…”
Section: Metabolic Postbiotics In Anemiamentioning
confidence: 99%
“…[15][16][17] Previous animal studies showed that inulin or FOS enhanced iron absorption. [18][19][20][21][22] Furthermore, most studies on rat models indicate a 10% (w/w) supplementation of inulin or FOS could enhance mineral absorption. [23][24][25] Higher dose could repress feed intake, whereas below 10% could lead to compromised effect or no effect.…”
Section: Introductionmentioning
confidence: 99%